The Analysis Of Grammatical Cohesion Reference In Jack Ma Speech Text “Believe In Your Dreams” - Diniati Andre Come Rihi; I Gede Neil Prajamukti Wardhana (Denpasar Institute, 2022)
The objective of this study is to analyze the grammatical cohesion reference of Jack Ma speech text “Believe in your dreams”. The study used descriptive qualitative method. This study aimed to figure out the types of reference in the speech text and to give an explanation of the reference used in the speech. The source of data in this study is Jack Ma speech text “Believe in your dreams”. The technique of collection data in this study used documentary. The technique of analysis data in this study is related to the theory, concepts, and methods of cohesion theory. This study used Cohesion in English by Halliday and Hasan. The finding in this study showed that there are two types of reference found in Jack Ma speech text “Believe in your dream”. In this speech text there are 36 utterances consist of 30 personal references and 6 demonstrative references. From the finding it was concluded that the most dominant type is personal reference in the speech text